Classroom walkthroughs as an effective strategy for preschool improvement during the COVID-19 lockdowns: a Chinese model - Xie, Sha; Yin, Hong; He, Mengyun; Li, Hui (Frontiers in Psychology, 2023)
Classroom walkthroughs are a widely used strategy for school improvement, varying over contexts and times. This study aims to explore the Chinese model of classroom walkthroughs in early childhood settings (ECS) during the COVID-19 lockdowns through a triangulated qualitative study. First, a group of ECS leaders (N = 15; M year of teaching experience = 18.87, SD = 7.74, range = 6 - 33 years) and a group of teachers (N = 15; M year of teaching experience = 8.40, SD = 3.96, range = 3 - 19 years) were interviewed in early 2022, and leaders’ observations notes were reviewed. The interview data were transcribed, recoded, and analyzed using an inductive approach, and the walkthrough documents were examined as a triangulation. Four themes and thirteen subthemes emerged from the interview data: content, pedagogical skills, tasks, and challenges pertaining to classroom walk-throughs. Two major challenges against efficient classroom walkthroughs during the COVID-19 lockdowns were found: building community and feeding forward. Based on the results, a Chinese model of classroom walkthrough was proposed. Implications for quality improvement were also addressed.